Evaluating ventilation for thermal comfort in two classrooms types in Malaysian secondary classrooms - Faraj, Lilas; Ja’afar, Mohamad Fakri Zaky; Shari, Zalina (International Information and Engineering Technology Association, 2023)
This study aimed at evaluating the ventilation quality in two secondary school buildings in Malaysia with two different layouts, representing one single- and one double-loaded-corridor design model. One classroom was chosen from each school for the study. In this study, the method uses computer simulations and user surveys to compare results on designing future secondary schools in Malaysia. DesignBuilder software were used to simulate the exterior and interior airflow, temperature, and humidity for various times of the year, with data collected from the simulations were fed into and analyses through the online CBE Thermal Comfort Tool to determine thermal comfort performance by using adaptive approach method. The simulations were performed for the same locations, on the same dates, and under the same environmental conditions to obtain comparable results. The simulation data were used to split the classrooms into thermal zones, with the thermal comfort rate for each zone being determined on the specified dates. A user survey to determine satisfaction levels and obtain comments was conducted with 67 participants (all students plus three teachers from each classroom). It was found that the single-loaded-corridor system provided greater thermal comfort throughout the year due to reduced temperatures and enhanced airflow.